Participatory cartographies in environmental and territorial education. Case study in Canelones, Uruguay - Lucía Eluén Morixe; Marcel Achkar; Ana Domínguez (Universidade Federal do Norte do Tocantins, 2024)
Based on research in the "Rincón de Santa Lucía" Park in Canelones, Uruguay, a strategy is presented for the production of knowledge that seeks to empower local communities in the appropriation and control of the natural commons. It proposes the generation of a set of environmental cartographies at a local scale, with the territorial agents of the area, which integrates the social appropriation of nature and contributes to the sustainable environmental management of the park's natural commons. For this purpose, different cartographic construction strategies were used: technical, perceptive and participatory maps. From the integration of the information generated, a local-scale Geographic Information System was built. The cartographies made it possible to evaluate variables, constructing an indicator that zoned the environmental vulnerability of the area, as a high potential tool for decision-making. The participatory knowledge production processes showed that it is possible to produce cartographies with high academic value, while recognizing and reinforcing identity territorialities. The integration of environmental education strategies with participatory mapping in public policies will make it possible to assist these processes from the pedagogy of Alternance and the epistemology of praxis.